2019
DOI: 10.1007/s42452-019-0428-1
|View full text |Cite
|
Sign up to set email alerts
|

Geostatistical modeling of dengue disease in Lahore, Pakistan

Abstract: Dengue outbreak has become a significant mosquito-borne disease in Pakistan with the worst outbreak in the Lahore district in 2011. This situation has emerged as a serious concern for disaster management authorities, and managing risks of dengue outbreaks has become their top priority. This study investigated the relationship of the reported dengue cases in the Lahore district in 2011 with the spatial and temporal changes in climatic and environmental factors. The quantitative co-relational research method was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Many researchers (Ali & Ahmad, 2018 ; Dom et al, 2016 ; Hassan et al, 2012 ; Khormi & Kumar, 2012 ; Latif & Mohamad, 2015 ; Ong et al, 2018 ; Panhwer et al, 2017 ; Pathirana et al, 2009 ; Saravanabavan et al, 2019 ; Shafie, 2011 ; Tariq & Zaidi, 2019 ; Tsheten et al, 2021 ; Withanage et al, 2021 ) identified the dengue risk zones using GIS techniques. Ali and Ahmad, ( 2018 ) demarcated the dengue risk zones in the Kolkata Municipal Corporation using the GIS and AHP method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many researchers (Ali & Ahmad, 2018 ; Dom et al, 2016 ; Hassan et al, 2012 ; Khormi & Kumar, 2012 ; Latif & Mohamad, 2015 ; Ong et al, 2018 ; Panhwer et al, 2017 ; Pathirana et al, 2009 ; Saravanabavan et al, 2019 ; Shafie, 2011 ; Tariq & Zaidi, 2019 ; Tsheten et al, 2021 ; Withanage et al, 2021 ) identified the dengue risk zones using GIS techniques. Ali and Ahmad, ( 2018 ) demarcated the dengue risk zones in the Kolkata Municipal Corporation using the GIS and AHP method.…”
Section: Literature Reviewmentioning
confidence: 99%